Soluble BTN2A1 Is a Potential Prognosis Biomarker in Pre-Treated Advanced Renal Cell Carcinoma - Billon, Emilien; Chanez, Brice; Rochigneux, Philippe; Albiges, Laurence; Vicier, Cécile; Pignot, Géraldine; Walz, Jochen; Chretien, Anne-Sophie; Gravis, Gwenaelle; Olive, Daniel (Frontiers in Immunology, 2021)
The development of immune checkpoint inhibitors (ICI) has dramatically changed the landscape of therapies for metastatic renal cell carcinoma. However, many patients do not benefit from such therapy and prognostic or predictive validated biomarker validated for ICI are still needed to better select and treat patient. Plasmatic soluble immune checkpoints have been described as potential immune biomarkers in hematological malignancies and solids tumors, then, we would like to explore the prognostic value of different soluble immune checkpoints in patients with mRCC treated with nivolumab after TKI. We prospectively collected plasma samples before nivolumab infusion from 38 patients previously treated for mRCC with TKI at Paoli-Calmettes Institute, from the NIVOREN GETUG-AFU 26 study (NCT03013335). Enzyme-linked immunosorbent assays (ELISA) were performed for soluble forms of PD-1, PD-L1, global BTN3, BTLA, BTN3A1 and BTN2A1. Among the different soluble checkpoints analyzed, only high baseline plasmatic level of BTN2A1 was significantly associated with shorter PFS: median PFS was 3.95 months for sBTN2A1high vs 14.30 months for sBTN2A1low (sBTN2A1 cut-off: 6.7ng/mL; HR = 2.26, 95%CI [0.68 – 4.60], p = 0.0307). There was no statistical difference in OS between sBTN2A1high and sBTN2A1low. Our results suggest that the baseline level of plasmatic BTN2A1 could be an independent prognosis factor of PFS after nivolumab for pre-treated patient with mRCC. However, these results need to be validated in a larger prospective cohort and the biological role of BTN subfamily and γδ T cell immunity in mRCC must be elucidated.